User authentication model using zero watermarking based on RGB images - Poddubnyi, Vadym; Sievierinov, Oleksandr (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2025)
The subject of the research is the methods and schemes of user authentication in information and communication networks. The aim of the work is to develop a user authentication model in information and communication systems using the zero-watermarking method based on RGB images. Objectives: to examine the main issues arising during the integration of access control systems; to develop a user authentication model using zero-watermarking; to study potential characteristics and put forward proposals/recommendations for its application in authentication; to construct graphical schemes that illustrate processes and procedures. Methods used: modeling methods and formal description methods. Results achieved: an improved user authentication model based on the zero-watermarking algorithm has been proposed as an alternative to existing authentication schemes in information and communication systems; its potential characteristics have been studied, confirming the prospects of the development; graphical representations of processes and procedures have been constructed. Conclusions: in the course of the work, the main problems faced by owners of information and communication systems during the integration of authentication systems were briefly reviewed; an improved authentication model using zero-watermarking was proposed. The zero-watermarking method is based on RGB images employing K-means clustering and DWT, while a password is used as the second factor. Three operating modes are presented: registration, authentication, and modification of key authentication data. This model serves as an alternative to existing schemes and can potentially reduce the cost of authentication, lower Type I and Type II error rates compared to similar authentication schemes, and improve the convenience of authentication in information and communication systems. It also expands the range of authentication schemes available to system owners during integration.